A platform for women's experiences? a case of the hip hop scene in Grahamstown, Eastern Cape - Kabwato, Sasha Nyasha (Rhodes University, Faculty of Humanities, Department of Sociology, 2019)
The main aim of this research is to examine the hip hop scene in Grahamstown, Eastern Cape and whether hip hop can serve as a significant platform to discuss women's lived experiences. This study also places focus on how female rappers construct their rap personas, as well as how they are perceived by their male counterparts. In order to understand the multifaceted viewpoints, it was necessary to interview both male and female hip hop artists. Eight interviews were conducted with eight young black rappers who are actively involved in the Grahamstown hip hop scene. It was found that hip hop, like any other art form, is a significant platform for women to express themselves, however gender constraints limit who is willing to listen to and promote their music. Male rappers advocate for women to talk about their stories, yet are more unlikely to listen because it does not relate to their struggles. In addition, there seem to be four specific tropes that female rappers choose to construct their identities from. Female rappers tend to create their personas around: Queen Mother, Fly Sista, Bitch with Attitude, and Lesbian. However, these categories are fluid and it was found that women navigate these categories depending on their audience and message they want to convey at a particular moment. Lastly, there is a split between Grahamstown West (Rhodes University) and Grahamstown East (township). University students are unlikely to perform in the township, and township residents rarely perform at organised events in Grahamstown West. In addition, Rhodes University students are more likely to feature on the university run radio station, rather than Radio Grahamstown, the local community radio.
Keywords: Hip-hop -- South Africa -- Makhanda; Popular culture -- South Africa -- Makhanda; Rap musicians -- South Africa -- Makhanda; Musicians, Black -- South Africa -- Makhanda; Women musicians, Black -- South Africa -- Makhanda; Women, Black -- South Africa -- Makhanda -- Psychology